2014
DOI: 10.1161/circep.114.001788
|View full text |Cite
|
Sign up to set email alerts
|

Near-Fatal Coronary Artery Spasm During Cryoballoon Pulmonary Vein Isolation

Abstract: A 50-year-old nonsmoker with paroxysmal atrial fibrillation was referred to our hospital for pulmonary vein isolation (PVI). He had a known 1-vessel coronary artery disease. Because of stable angina, a drug-eluting stent had been implanted into the midportion of the left anterior descending artery in 2010. Otherwise he was healthy. His medical treatment included warfarin, sotalol, an angiotensin-converting enzyme-inhibitor and a statin. Cryoballoon-PVI (Arctic Front Advance 28 mm; Medtronic) was scheduled unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…Some cases with a cryoenergy-induced coronary artery spasm by CB ablation and cryocatheter ablation were reported. 3 , 4 These reports speculated the cause of coronary artery spasm as a cryoenergy-induced blood cooling. However, the coronary spasm site was not necessarily close to the cryoapplication site, and an indirect effect owing to blood cooling was suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases with a cryoenergy-induced coronary artery spasm by CB ablation and cryocatheter ablation were reported. 3 , 4 These reports speculated the cause of coronary artery spasm as a cryoenergy-induced blood cooling. However, the coronary spasm site was not necessarily close to the cryoapplication site, and an indirect effect owing to blood cooling was suggested.…”
Section: Discussionmentioning
confidence: 99%
“… 1 On the other hand, several complications, such as esophageal erosions and phrenic nerve injuries, have been reported with AF ablation using second-generation CB. 2 Lehrmann and colleagues 3 have reported a case of near-fatal coronary artery spasm during PVI using second-generation CB. In this case, the mechanism of coronary artery spasm was speculated as cryoenergy-induced blood cooling, which was attributable to the close proximity between the CB and coronary artery spasm site.…”
Section: Introductionmentioning
confidence: 99%
“…Some cases of coronary spasms related to PV isolation by radiofrequency ablation have been reported that suggested direct thermal effects on the coronary artery and also a possible indirect effect that could induce coronary spasms through the autonomic nervous system 1, 2. A case of near-fatal left main coronary spasms following a cryoablation procedure was also reported 3 . That report suggested the possibility of an indirect effect on the coronary artery because an ST-T change was already observed after starting the first cryoenergy application for the LSPV, which is somewhat distant from the left main coronary artery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cryoballoon-induced CAS is also reported. 3,12 As more extensive and complicated ablations are performed for drug-refractory AF, the incidence of ablation-induced CAS may increase. Therefore, the postprocedural observation and recognition of this rare but potentially life-threatening complication will improve the conventional practice of catheter ablation for patients with drug-refractory atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%